2019
DOI: 10.1038/s41598-019-45741-8
|View full text |Cite
|
Sign up to set email alerts
|

Simulated microgravity modulates the mesenchymal stromal cell response to inflammatory stimulation

Abstract: The duration and distance of manned space flights emphasizes the importance of advanced elucidation of space flight factors and their effects on human beings. The exposure to inflammatory mediators under microgravity may contribute to the activity of different cells, perivascular stromal cells (MSCs) in particular. Inflammatory activation is now considered as a principal cue of MSC engagement in reparative remodeling. In the present paper, the effect of simulated microgravity (sµg) on TNFα-mediated priming of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Several studies investigating the impact of µ g on the behaviour and health of mice on the ISS were published in this Collection 1823 , in addition to investigations at the cellular level in space 24 and in short-term µ g provided by PF maneuvers 25 . Moreover, cell studies in simulated (s-) µ g at ground-based facilities are included in this Collection 2630 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies investigating the impact of µ g on the behaviour and health of mice on the ISS were published in this Collection 1823 , in addition to investigations at the cellular level in space 24 and in short-term µ g provided by PF maneuvers 25 . Moreover, cell studies in simulated (s-) µ g at ground-based facilities are included in this Collection 2630 .…”
mentioning
confidence: 99%
“…3D clinorotation was used to study mesenchymal stromal cell (MSC) response to inflammatory stimulation 26 . A reduced response of MSCs to priming in µ g might also indicate less involvement of these cells in tissue remodelling 26 . Arun et al .…”
mentioning
confidence: 99%
“…Several studies have reported that c-fos and c-Jun are regulated in simulated microgravity ( Shi et al, 2021 ). Furthermore, ICAM-1, a transmembrane protein expressed on the surface of epithelial cells, endothelial cells, T cells, and macrophages, was also demonstrated to respond to microgravity stimulation ( Buravkova et al, 2018 ; Lü et al, 2019 ; Nassef et al, 2019 ; Ratushnyy et al, 2019 ). ICAM-1 expression was observed to decrease quickly and reversibly on the surface of BV-2 cells following the microgravity phase in parabolic flight, but in long-term microgravity induced by orbital SIMBOX/Shenzhou-8, ICAM-1 expression increased in macrophage-like differentiated human U937 cells ( Paulsen et al, 2015 ).…”
Section: Mechanistic Assumptions Of Microglial Activation In Microgra...mentioning
confidence: 99%
“…Other immune responses are also affected by a low-shear environment; inflammation, specifically adaptation of the vasculature (release of vasoactive factors [119]), is determined by the vessel wall state which composes of endothelial cells and mesenchymal stem cells [120]. Microgravity analogues have been shown to exacerbate the effect of endothelial cell activation by inflammatory mediators [121].…”
Section: Cell-cell Interactionsmentioning
confidence: 99%